(untitled) (Comprehensive Journal of Science, 2025)
This research, titled “The Participation of Women in Parliamentary Councils and Ministries: An Analytical Study in Light of the Evidence of the Permissive and Prohibitive Views,” addresses a contemporary issue that has sparked legal and intellectual debate. The issue concerns the legitimacy of women holding high political positions, such as membership in parliamentary councils and ministerial posts. This is done through a comparative analytical study of the evidence provided by both the permissive and prohibitive groups. The research begins by defining the parliamentary council linguistically as stemming from the Arabic word “النَّوْب,” meaning rotation or succession. Term-wise, it refers to a representative body that contributes to legislation and monitors the executive authority. As for the ministry, it means linguistically “bearing a weight” or “burden,” and term-wise, it refers to an executive position held by individuals responsible for managing state affairs within defined competencies. The research then presents the evidence of those who permit women in these roles, including the general call for legal accountability, women’s participation in public life during the time of the Prophet Muhammad (peace be upon him), and the principle of achieving public welfare. It also counters the evidence of those who oppose women’s participation, arguing that the prohibitive proofs do not constitute a solid argument for an absolute ban. The research also reviews the evidence of the prohibitive group, primarily the Hadith: “A people will never succeed who entrust their affairs to a woman,” and their belief that leadership should be exclusively for men. The research refutes this, explaining that the Hadith is specific to the highest leadership positions and does not necessarily apply to more specific roles such as parliamentary membership or ministerial posts. The research concludes that the prevailing opinion is that women’s participation in parliamentary and ministerial positions is permissible, provided they meet the necessary qualifications and conditions. The participation should align with Islamic guidelines, particularly ensuring that the woman adheres to the appropriate Islamic rules when engaging in political work.